The hypoglycemic and renal protective effects of Grifola frondosa polysaccharides in early diabetic nephropathy. Issue 12 (11th October 2020) - Jiang, Tao; Wang, Liang; Ma, Angjie; Wu, Yi; Wu, Qiwen; Wu, Qiulin; Lu, Jianwei; Zhong, Tian
Abstract: Grifola frondosa is a basidiomycete polypore fungus. Polysaccharides from G. frondosa (PGF) has recently attracted attention for its various physiological activities including antioxidant, antitumor, and anti‐fatigue effects. In this study, hypoglycemic activity of PGF and its preventive effect against the progression of kidney fibrosis in Diabetic nephropathy (DN) rats were investigated. The results showed that PGF led to a significant decrease in fasting blood glucose levels and an increase in body weight in the treatment group compared with those of model group. Serum biochemical indexes including N‐acetyl‐β‐D‐glucosaminidase (NAG), blood urea nitrogen (BUN), serum creatinine (SCr), and urine microalbumin (u‐mAlb) levels of PGF‐treated group were significantly lower than those of model group. Inflammatory cytokines and renal fibrosis indexes of PGF group were also decreased compared to the model group. The whole results demonstrated the renal‐protective effects of PGF via reducing the inflammatory factor content and preventing renal fibrosis. Practical applications: G. frondosa constitutes a rich source of polysaccharides, steroid, and phenolic compounds. The results obtained revealed that the purified PGF have the effect of reducing inflammation cytokines and renal fibrosis indexes. These two factors are associated with the development and progression of diabetic nephropathy. Therefore, PGF may produce both hypoglycemic and renal‐protective effects, and potentially be of use as a functional food for the treatment or prevention of diabetic nephropathy. Abstract : Hypoglycemic activity of polysaccharide of Grifola frondosa and its preventive effect against the progression of kidney fibrosis in Diabetic nephropathy rats were investigated. The results showed that compared with the control group, PGF led to a significant increase in body weight and decrease in fasting blood glucose levels in the treatment group. Also, Serum biochemical indexes, inflammatory cytokines and renal fibrosis indexes of the treatment group were all significantly lower than those of the control group.